2015
DOI: 10.1016/j.alit.2015.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments regarding periostin in bronchial asthma

Abstract: Although it is currently recognized that bronchial asthma is not a single disease but a syndrome, we have not yet made use of our new understanding of this heterogeneity as we treat asthma patients. To increase the efficacy of anti-asthma drugs and to decrease costs, it is important to stratify asthma patients into subgroups and to develop therapeutic strategies for each subgroup. Periostin has recently emerged as a biomarker for bronchial asthma, unique in that it is useful not in diagnosis but in categorizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 54 publications
0
46
0
1
Order By: Relevance
“…Periostin is an extracellular matrix (ECM) protein belonging to the fasciclin family, based on its homology to fasciclin 1 (FAS1) 123. Periostin also acts as a matricellular protein that functions in cell activation by binding to its receptors, several integrins—α V β1, α V β3, α V β5, α 6 β4, and α M β 2 —on the cell surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Periostin is an extracellular matrix (ECM) protein belonging to the fasciclin family, based on its homology to fasciclin 1 (FAS1) 123. Periostin also acts as a matricellular protein that functions in cell activation by binding to its receptors, several integrins—α V β1, α V β3, α V β5, α 6 β4, and α M β 2 —on the cell surface.…”
Section: Introductionmentioning
confidence: 99%
“…The actions of periostin as both an ECM protein and as a matricellular protein are important for the development and remodeling of many tissues, such as bone, heart, and skin 12. Moreover, it has been revealed that periostin plays an important role in allergic inflammation, including asthma 234. Based on these findings, much attention has been paid to periostin as a useful biomarker for treating asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Improved identification of patients whose disease has a “T H 2 endotype”[31,35], using biomarkers including periostin[39,40] and high levels of blood eosinophils[41], has been used to recommend therapies targeting T H 2 response components (e.g., IL-4, IL-5, IL-13 and/or their receptors)[4247]. However, it appears that there are many pitfalls in attempts to develop these new diagnostic categories for patient populations differing by age, race, or other factors that may alter the correlation of disease phenotype with individual biomarkers.…”
Section: Therapy Selection and Monitoringmentioning
confidence: 99%
“…While this is an active area of research, there already are data indicating that patients whose asthma is associated with elevated levels of biomarkers of a "T H 2 phenotype", 12,25 including periostin 26,27 and high levels of blood eosinophils, 28 will benefit more from therapy targeting elements of the T H 2 response (e.g., IL-4, IL-5, IL-13 and/or their receptors) than will patients with low levels of such biomarkers. [29][30][31][32][33][34] However, recent data indicate that such "biomarkers" may be more useful in some patient subpopulations than others.…”
Section: Medicine and Precision Health"mentioning
confidence: 99%